2019
DOI: 10.1371/journal.pone.0222843
|View full text |Cite
|
Sign up to set email alerts
|

Practice and factors associated with active management of third stage of labor among obstetric care providers in Amhara region referral hospitals, North Ethiopia, 2018: A cross sectional study

Abstract: BackgroundActive management of third stage of labor is the most indispensable intervention to avert post-partum hemorrhage which is one of the typical causes of maternal morbidity and mortality. Therefore, the aim of the study was to assess practice and factors associated with active management of third stage of labor among obstetric care providers in referral hospitals.MethodsInstitution based cross-sectional study design was conducted from April 1–30, 2018. Simple random sampling technique was used to select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
2
7
1
Order By: Relevance
“…This study showed a statistical significance between experience in the labour ward and the management of PPH. This is in line with a study by Adane et al in northern Ethiopia which showed similar findings 12 .…”
Section: Discussionsupporting
confidence: 93%
“…This study showed a statistical significance between experience in the labour ward and the management of PPH. This is in line with a study by Adane et al in northern Ethiopia which showed similar findings 12 .…”
Section: Discussionsupporting
confidence: 93%
“…HCPs in our study who were having degree in nursing and medicine had almost twofold higher odds of adequate knowledge in AMTSL compared to women. This is contrary to what was reported in a study of Adane et al, in which male health care providers were associated with good practice (AOR = 1.74, 95% CI 1.03-2.94) [1].…”
Section: Discussioncontrasting
confidence: 99%
“…Author details 1 Department of Obstetrics and Gynecology, Bugando Medical Center, Mwanza, Tanzania. 2 Department of Clinical Nursing, School of Nursing and Public Health, The University of Dodoma, Dodoma, Tanzania.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active management of the third stage of labor is critical in reducing PPH occurrence but is influenced by many factors, including standard guidelines and protocols, quick service accessibility, availability of resources (equipment and staff), and quality of care services [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%